Flower Bulb Waste Material is a Natural Niche for the Sexual Cycle in Aspergillus fumigatus - Zhang, Jianhua; Verweij, Paul E.; Rijs, Antonius J. M. M.; Debets, Alfons J. M.; Snelders, Eveline (Frontiers in Cellular and Infection Microbiology, 2022)
With population genetic evidence of recombination ongoing in the natural Aspergillus fumigatus population and a sexual cycle demonstrated in the laboratory the question remained what the natural niche for A. fumigatus sex is. Composting plant-waste material is a known substrate of A. fumigatus to thrive and withstand temperatures even up to 70°C. Previous studies have shown indirect evidence for sexual reproduction in these heaps but never directly demonstrated the sexual structures due to technical limitations. Here, we show that flower bulb waste material from stockpiles undergoing composting can provide the conditions for sexual reproduction. Direct detection of ascospore structures was shown in agricultural flower bulb waste material by using a grid-based detection assay. Furthermore, we demonstrate that ascospores can germinate after exposure to 70°C for up to several days in contrast to asexual conidia that are unable to survive a two-hour heat shock. This indicates a sufficient time frame for ascospores to survive and escape composting stockpiles. Finally, sexual crosses with cleistothecium and viable ascospore formation could successfully be performed on flower bulb waste material. Recombination of A. fumigatus can now be explained by active sexual reproduction in nature as we show in this study that flower bulb waste material provides an environmental niche for sex.